Politicizing power between the imperial female and the Malay other in Emily Innes’s The Chersonese With The Gilding Of - Ismail, Hanita Hanim; Wan Yahya, Wan Roselezam (Australian International Academic Centre, 2016)
The autobiographical writing by Emily Innes’s The Chersonese with the Gliding offer corded experiences and turbulence underwent by a White officer’s wife to Malaya with an underlying western perspectives and impression on the country during pre-Independence period and its people. By using narrative data, this article examines existing power relations, framed within interactions between the white lady (representing the Self) and her Malay male servants (as the Other). The use of Michel Foucault’s Technology of Power enables an analysis of power strategies that represent both binary opposites in order to also trace the existence of gender power. More specifically, it allows a protoconceptualisation of types among Malay men that are identifiable during the pre-Independence period. Further understanding the Malay men, especially of their ego, is important in the growing interest over Postcolonial subject where it explores forms of resistance, portrayed by the Other in his daily power relation with the Self. Findings reveal that while power play exists within these interactions, it is a one-sided discourse which sanctions fair play as well as equality of power distribution.